Knowledge of the residents at King Abdul-Aziz University Hospital (KAAUH) about palliative care - Sultan H Alamri (Wolters Kluwer Medknow Publications, 2012)
Background: Palliative care is a rapidly growing subspecialty that aims at improving the quality of life and relieving suffering associated with life threatening disease. Despite its rapid growth and huge demand, the knowledge of health care professionals on palliative care remains inadequate. Objective: This study aims to determine the knowledge of residents at King Abdul-Aziz University Hospital (KAAUH) on palliative care. Materials and Methods: Through a cross-sectional design, all residents in the hospital were invited to complete a two-part self-administered questionnaire in June 2010. The first part of the questionnaire included variables describing the socio-demographic characteristics and educational background, and the second part developed by palliative care education initiative at Dalhousie University in Canada in 2000 had 25 items on the knowledge of palliative care. Results : Of the 80 residents 65 (81%) responded, the overwhelming majority of whom were Saudis (92.3%) with an equal representation of males and females. The mean age of the participants was 29.1 ± 2.4 years. Less than one-third (29.2%) indicated that they had previous didactic education on palliative care. The percentage of right answers on items reflecting knowledge on palliative care accounted for 29.9% ± 9.9%. No statistically significant difference was found in the level of knowledge among the residents according to their demographics or graduation and training characteristics. Conclusion: Resident physicians enrolled in postgraduate programs have suboptimal knowledge of basic palliative care. Substantial efforts should be made to incorporate a palliative care module into the theoretical and practical training of medical students and resident physicians.